Budgeting for a billion: applying health technology assessment (HTA) for universal health coverage in India - Saudamini Vishwanath Dabak; Songyot Pilasant; Abha Mehndiratta; Laura Emily Downey; Francoise Cluzeau; Kalipso Chalkidou; Alia Cynthia Gonzales Luz; Sitaporn Youngkong; Yot Teerawattananon (BMC, 2018)
Abstract Background India recently launched the largest universal health coverage scheme in the world to address the gaps in providing healthcare to its population. Health technology assessment (HTA) has been recognised as a tool for setting priorities as the government seeks to increase public health expenditure. This study aims to understand the current situation for healthcare decision-making in India and deliberate on the opportunities for introducing HTA in the country. Methods A paper-based questionnaire, adapted from a survey developed by the International Decision Support Initiative (iDSI), was administered on the second day of the Topic Selection Workshop that was conducted as part of the HTA Awareness Raising Workshop held in New Delhi on 25-27 July, 2016. Participants were invited to respond to questions covering the need, demand and supply for HTA in their context as well as the role of their organisation vis-à-vis HTA. The response rate for the survey was about 68% with 41 participants having completed the survey. Results Three quarters of the respondents (71%) stated that the government allocated healthcare resources on the basis of expert opinion. Most respondents indicated reimbursement of individual health technologies and designing a basic health benefit package (93% each) were important health policy areas while medical devices and screening programmes were cited as important technologies (98% and 92%, respectively). More than half of the respondents noted that relevant local data was either not available or was limited. Finally, technical capacity was seen as a strength and a constraint facing organisations. Conclusion The findings from this study shed light on the current situation, the opportunities, including potential topics, and challenges in conducting HTA in India. There are limitations to the study and further studies may need to be conducted to inform the role that HTA will play in the design or implementation of universal health coverage in India.